Please someone help me get the answers to these two!
![Please someone help me get the answers to these two class=](https://us-static.z-dn.net/files/daf/5a5a7864441a6fb124047ee9baac209c.png)
![Please someone help me get the answers to these two class=](https://us-static.z-dn.net/files/d6c/f996adfd9bbb9c1346cd0e1ad9a3d46d.png)
Answer:
Step-by-step explanation:
(-3, 411):
a*b^(-3) + d = 411 (1)
(1, 11):
a*b + d = 11 (2)
horizontal asymptote y = 6 when x -> ∞, so d = 6
so (1) becomes ab^(-3) + 6 = 411, or ab^(-3) = 405 (3)
(2) becomes ab + 6 = 11, or ab = 5 (4)
(4)/(3): b⁴ = 5/405 = 1/81 = 1/3⁴, so b = 1/3
From (4) a = 5/b = 15
Then
f(x) = 15(1/3)^x + 6